Are first responders prepared for electric vehicle fires? A national survey. (January 2023) - Liu, Jun; Xu, Ningzhe; Shi, Yangming; Barnett, Timothy; Jones, Steven
Highlights: A national survey in the United States to gather first responders' perceptions towards EVs in traffic incidents. Over 1000 first responders from 50 states and Washington DC participated in a survey. More than 40% of first responders reported never receiving EV safety training. Safety training is highly related to the level of EV fire knowledge among first responders. Paramedics or EMS personnel are associated with the highest odds of not receiving EV safety training. Abstract: Transitioning to electric vehicles (EVs) will create both opportunities and challenges. Although some programs and resources related to EVs have been made available to first responders, it remains unknown whether our first responders are well prepared for traffic incidents that involve EVs and whether there are any organizational and geographic disparities in preparedness. To answer these questions, a national survey was conducted to collect feedback on responders' incident management knowledge and training experiences related to EVs, as well as their attitudes and concerns towards EVs. Over 1000 first responders across the country participated in the survey, and the survey had representation from all 50 states and Washington DC. Over 40% of first responders reported never receiving EV-related safety training. Paramedics or EMS are associated with the highest odds of not receiving EV-related training, followed by law enforcement. Geographically, FEMA Region 8 (e.g., Montana and North Dakota) is associated with the highest percentage of not receiving EV training. Regarding EV fire tactics, more than half (57%) of law enforcement officers said they do not know any; responders from towing & recovery also have little knowledge compared to firefighters. Statistical modeling was conducted to explore correlates of responders' EV safety training and knowledge of EV fire tactics. The survey also provided insights about the challenges and risks of managing EV-involved incidents. In summary, responders are greatly concerned about the risks that EVs can pose to their community, and actions must be taken now.